Adhesividad de oligolignóles sintéticos y naturales - Sedano Mendoza, Miriam (Universidad Michoacana de San Nicolás de Hidalgo, 2010)
The aim of this project is to compare the interaction energies by theoretical and experimental methods between the most frequent dimers and trimmers in lignins. The methodology was divided into two phases. A theoretical phase where is obtained the interaction energy of the lignans on a substrate of crystalline cellulose composed by 3 superimposed lattices (6x6x3 model). The procedure in this case is to find the interaction energy by docking method. When the lignan is approached to the cellulose surface, its conformation changes to adapt itself on the cellulose surface to minimize the total energy in the system until the position and conformation of minimum energy is reached. In this precise case we found that the trimmer’s present stronger adherence with the substrate than dimers but, this result is always according to the substrate. In the experimental phase, we followed two strategies to obtain dimers and trimmers. The first strategy was the synthesis and analysis of lignans by Nuclear Magnetic Resonance (NMR). The second process was their localization in natural lignins by spectrometry of Matrix Assisted Laser Desorption Ionization Time-Of-Flight (MALDI-TOF). Then, their resistances were measured in a cellulose sheet by Thermo-mechanic Analysis (TMA) in the tensile test. Finally we found a correlation between the energy of lignan-subtract interaction by molecular mechanics and the adhesive strength by experimental test. Thus we can say that lignins with high quantity of trimmers inside its structure present a stronger interaction with the substrate. The molecular mechanics calculations indicated that a dimer O4-linked has stronger attraction for the substrate than - or -5-linked dimers. Consequently the bond energy is given by molecular weight and type of linkage. Hence lignans with higher molecular weight and O4-links have a better adhesion in the cellulose substrate.

El objetivo de este proyecto es obtener una comparación de energías de enlace por métodos teóricos y experimentales entre los dímeros y trímeros más frecuentes en las ligninas. En la fase teórica, se obtuvo la energía de enlace para cada uno de los lignanos sobre un sustrato de celulosa cristalina, compuesto por 3 capas de 6 por 12 glucosas cada una. El procedimiento consistió en determinar la energía de anclaje molecular, donde el lignano interacciona con el bloque de celulosa cambiando su conformación repetidas veces hasta su adaptación con la superficie de ésta y reduciendo al máximo la energía total del sistema. En este caso preciso, se encontraron que los trímeros presentan mayor adherencia al sustrato que los dímeros. Más sin embargo, éste resultado siempre dependerá de la naturaleza del sustrato y de las condiciones de interacción. En la fase experimental, se siguieron dos estrategias para obtener los dímeros y trímeros. La primera estrategia fue la síntesis y el análisis de los lignanos por resonancia magnética nuclear. La segunda estrategia fue su localización en ligninas naturales por espectrometría de masas. Posteriormente se midió la resistencia adhesiva a tensión en una hoja de celulosa por el análisis termo-mecánico. Finalmente se encontró una correlación entre los resultados teóricos y experimentales de sus energías de enlace. Con lo cual, se puede decir que ligninas con alta cantidad de trímeros presentan una interacción más fuerte con el sustrato de celulosa. De acuerdo con los resultados se tiene que un dímero con un enlace tipo -O-4 presentará una atracción más fuerte al sustrato que los dímeros con enlace tipo - o -5. Por consiguiente la masa molecular y el tipo de enlace son los factores predominantes en el cálculo de la energía de enlace en los lignanos.
Facultad de Ingeniería en Tecnología de la Madera. Maestría en Ciencias en Tecnología de la Madera
Keywords: info:eu-repo/classification/cti/7; FITECMA-M-2010-0002; Adhesividad; Oligognóles; Sintéticos; Naturales; Lignina; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/170